Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/nu13030713
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Selection Criteria for Probiotic Strains with High Potential for Obesity Management

Abstract: Since alterations of the gut microbiota have been shown to play a major role in obesity, probiotics have attracted attention. Our aim was to identify probiotic candidates for the management of obesity using a combination of in vitro and in vivo approaches. We evaluated in vitro the ability of 23 strains to limit lipid accumulation in adipocytes and to enhance the secretion of satiety-promoting gut peptide in enteroendocrine cells. Following the in vitro screening, selected strains were further investigated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…A recent study on the management of obesity [ 46 ] using the gut microbiota of mouse models showed that a combination of B. animalis subsp. lactis with Lactobacillus gasseri significantly limited the body weight gain and increase in body fat induced by a high-fat diet (HFD) ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on the management of obesity [ 46 ] using the gut microbiota of mouse models showed that a combination of B. animalis subsp. lactis with Lactobacillus gasseri significantly limited the body weight gain and increase in body fat induced by a high-fat diet (HFD) ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable evidence in pre-clinical and clinical interventions that demonstrates the use of probiotics as an alternative to improve the treatment and prevention of obesityrelated disorders (10,23). The different anti-obesity effects of traditional or not traditional probiotics strains are needed to be well-defined since its benefits are strains and/or dosedependent (24). It is crucial to understand the strain-specificity and mechanisms involved in probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro study showed that the mixture of Bifidobacterium lactis and Lactobacillus salivarius could promote the production of butyrate and propionate in the fermentation system [ 47 ]. Moreover, after comparing 23 bacteria strains, an experimental study revealed that Bifidobacterium longum PI10 and Ligilactobacillus salivarius PI2 could restrict lipid accumulation in adipocytes [ 70 ]. Furthermore, the Lactobacillus plantarum NK3 and Bifidobacterium longum NK49 could mitigate obesity and osteoporosis in mice by suppressing the production of lipopolysaccharide (LPS) from gut microbiota and downregulating nuclear factor kappa B (NF-κB)-linked tumor necrosis factor α (TNF-α) expression [ 71 ].…”
Section: Mechanisms Of Probiotics Prebiotics Synbiotics and Postbiotics On Metabolic Diseases By Targeting Gut Microbiotamentioning
confidence: 99%
“…Besides, the single administration of Lactobacillus fermentum MCC2759 and MCC2760 was both beneficial to diabetic rats, but the MCC2760 strain showed a slightly better improvement in the intestinal barrier and the expression of GLUT4, GLP1, and zonula occludens-1 (ZO-1) than the MCC2759 strain [ 72 ]. Moreover, Bifidobacterium longum PI10 was a highly potent inducer for GLP1 and interleukin-10 (IL-10), which could strengthen the intestinal barrier [ 70 ].…”
Section: Mechanisms Of Probiotics Prebiotics Synbiotics and Postbiotics On Metabolic Diseases By Targeting Gut Microbiotamentioning
confidence: 99%